2005
DOI: 10.1136/bmj.38636.593461.68
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and efficiency of search methods in systematic reviews of complex evidence: audit of primary sources

Abstract: Objective To describe where papers come from in a systematic review of complex evidence. Method Audit of how the 495 primary sources for the review were originally identified. Results Only 30% of sources were obtained from the protocol defined at the outset of the study (that is, from the database and hand searches). Fifty one per cent were identified by "snowballing" (such as pursuing references of references), and 24% by personal knowledge or personal contacts. Conclusion Systematic reviews of complex eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
1,147
2
21

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,546 publications
(1,235 citation statements)
references
References 4 publications
8
1,147
2
21
Order By: Relevance
“…Iako istraživačko pitanje često upućuje na određenu populaciju, postavke i ishode, takav koncept možda nije dobro opisan u naslovu članka ili sažetku. Zbog toga generalne baze podataka, poput baze Medline, za identificiranje studija za Cochrane pregledne članke uključuju tri glavna uvjeta: a) pojmovi za pretragu zdravstvenog stanja od interesa, b) uvjeti za traženje intervencije, c) uvjeti za traženje vrste studija koje će biti uključene (filtar) 10,11 . Nedostatno pretraživanje literature može rezultirati sustavnom pogreškom koja umanjuje vjerodostojnost i korisnost rezultata i zaključaka sustavnog preglednog članka.…”
Section: Pretraživanje Studija Temeljito Pretraživanjeunclassified
“…Iako istraživačko pitanje često upućuje na određenu populaciju, postavke i ishode, takav koncept možda nije dobro opisan u naslovu članka ili sažetku. Zbog toga generalne baze podataka, poput baze Medline, za identificiranje studija za Cochrane pregledne članke uključuju tri glavna uvjeta: a) pojmovi za pretragu zdravstvenog stanja od interesa, b) uvjeti za traženje intervencije, c) uvjeti za traženje vrste studija koje će biti uključene (filtar) 10,11 . Nedostatno pretraživanje literature može rezultirati sustavnom pogreškom koja umanjuje vjerodostojnost i korisnost rezultata i zaključaka sustavnog preglednog članka.…”
Section: Pretraživanje Studija Temeljito Pretraživanjeunclassified
“…Techniques such as "snowballing" otherwise referred to as reference tracking were also utilised. This method involves scanning reference lists of all full text papers and using judgment to decide whether to pursue texts further [7]. A systematic review was not conducted, as it was essential to locate literature outside databases containing published journals (text books, government and non for profit websites), as this is a regular repository for evaluation literature.…”
Section: Methodsmentioning
confidence: 99%
“…see reviews by Gallacher et al 13 , De Pinho Campos et al 32 and Hunter et al 33 ). Systematic reviews relating to policy making may fail to identify important evidence if they do not extend beyond database searching 34 , because evidence in the social sciences, social policy and case law may not be indexed in searchable electronic databases. 12 This review indicated that grey literature is a necessary component of social science systematic reviews 9,35 , despite the difficulty of conducting systematic searches for such literature and assessing its quality.…”
Section: Key Sources Of Evidence In the Grey Literaturementioning
confidence: 99%